Assessing Deep-Pelagic Shrimp Biomass to 3000 m in The Atlantic Ocean and Ramifications of Upscaled Global Biomass - Vereshchaka, Alexander L. (Sci Rep, 2019)
We assess the biomass of deep-pelagic shrimps in the Atlantic Ocean using data collected between 40°N and 40°S. Forty-eight stations were sampled in discrete-depth fashion, including epi- (0–200 m), meso- (200–800/1000 m), upper bathy- (800/1000–1500 m), and lower bathypelagic (1500–3000 m) strata. We compared samples collected from the same area on the same night using obliquely towed trawls and large vertically towed nets and found that shrimp catches from the latter were significantly higher. This suggests that vertical nets are more efficient for biomass assessments, and we report these values here. We further compared day and night samples from the same site and found that biomass estimates differed only in the epi- and mesopelagic strata, while estimates from the bathypelagic strata and the total water column were independent of time of day. Maximal shrimp standing stocks occurred in the upper bathypelagic (52–54% of total biomass) and in the mesopelagic (42–43%). We assessed shrimp biomass in three major regions of the Atlantic between 40°N and 40°S, and the first-order extrapolation of these data suggests that the global low-latitude deep-pelagic shrimp biomass (1700 million tons) may lie within the range reported for mesopelagic fishes (estimations between 1000 and 15000 million tons). These data, along with previous fish-biomass estimates, call for the reassessment of the quantity and distribution of nektonic carbon in the deep ocean.